Influence of Intestinal Microorganisms on Anastomotic Leakage after Colorectal Surgery - Rugieniūtė, Justina; Pažusis, Matas; Mačiulaitytė, Aistė; Černauskis, Karolis; Saladžinskas, Žilvinas (Lietuvos chirurgija, 2020)
Introduction. One of the most common and serious complications of near-postoperative surgery after colon resection with anastomosis is intestinal leakage with a frequency of 1 to 24%. Therefore, it is very important to evaluate the factors that may determine the development of this complication. One of the etiological factors behind the development of this complication is the intestinal microbiota, which is playing an increasingly important role in this process. Nevertheless, there is still a lack of comprehensive clinical evidence on the influence of the intestinal microbiota on postoperative complications such as anastomotic leakage. Purpose. To evaluate the influence of intestinal microorganisms on anastomotic leakage after elective intestines surgery. Methods. A prospective study was performed at the Lithuanian University of Health Sciences Hospital, Kaunas Clinics, Clinic of Surgery. There were included patients who underwent colon surgery (right hemicolectomy, left hemicolectomy, sigmoid resection and closure of ileostomy). Intestinal mucosal biopsy performed before restoring intestinal integrity and sent for microbiological and antibiotic examination. Patients were also observed postoperatively for anastomotic leakage. Results. The majority of patients were treated for colon cancer – 46 (92.0%). In 19 patients crop (38.0%) grown one microorganism, in 12 (24.0%) – 2 microorganisms, in 5 (10.0%) – 3 microorganisms, in 1 (2.0%) – 4 types of bacteria. In the most of the crops were observed growth by E. coli – 30 (60.0%), Enterococcus spp. – 12 (24.0%), Bacteroides spp. – 4 (8.0%), Klebsiella oxytoca – 2 (4.0%), Beta hemolytic streptococcus – 2 (4.0%) patients. Citrobacter fundii, Citrobacter brakii, Parabacteroides distasonis, Proteus mirabilis, Klebsiella pneumoniae, Enterobacteriaceae daacea grew only in 1 (2.0%) patients crop. Postoperative anastomotic leakage diagnosed in 2 (4.0%) patients. Conclusions. The major microorganisms that grown were E. coli. Due to the small sample, tendency can not be predicted, but microorganisms that promote small blood vessels thrombosis may be one of the factors that cause anastomotic leakage.